Medical nutrition therapy using plant-focused low-protein meal plans for management of chronic kidney disease in diabetes. Issue 1 (January 2022) - Kalantar-Zadeh, Kamyar; Rhee, Connie M.; Joshi, Shivam; Brown-Tortorici, Amanda; Kramer, Holly M.
Abstract : Purpose of review: Nearly half of all Americans with chronic kidney disease (CKD) also have type-2-diabetes (T2D). Whereas traditional and emerging pharmacotherapies are increasingly frequently used for the management of CKD in diabetes (CKD/DM), the role of integrated or multimodal interventions including the potentially synergistic and additive effect of diet and lifestyle modifications in addition to pharmacotherapy has not been well examined, in sharp contrast to the well-known integrated approaches to heart disease. Recent findings: Low-carbohydrate low-fat diets are often recommended in T2D, whereas low-protein diets (LPD) are recommended by guidelines for nondiabetic CKD with increasing emphasis on plant-based protein sources. High-protein diets with greater animal protein lead to glomerular hyperfiltration, especially in patients with T2D, and faster decline in renal function. Guidelines provide differing recommendations regarding the amount (low vs high) and source (plant vs animal) of dietary protein intake (DPI) in CKD/DM. Some such as KDIGO recommend 0.8 g/kg/day based on insufficient evidence for DPI restriction in CKD/DM, whereas KDOQI and ISRNM recommend a DPI of 0.6 to <0.8 g/kg/day. A patient-centered plant-focused LPD for the nutritional management of CKD/DM (PLAFOND), a type of PLADO diet comprising DPI of 0.6 to <0.8 g/kg/day with >50% plant-based sources, high dietary fiber, low glycemic index, and 25–35 Cal/kg/day energy, can be implemented by renal dietitians under Medical Nutrition Therapy. Summary: Potential risks vs benefits of high vs low protein intake in CKD/DM is unknown, for which expert recommendations remain opinion based. Randomized controlled studies are needed to examine safety, acceptability and efficacy of PLAFOND.